1994
DOI: 10.1111/j.1365-2249.1994.tb06564.x
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment and characterization of dendritic cells from human bronchoalveolar lavages

Abstract: SUMMARYIn the present study about 0-3% to 1-6% of human bronchoalveolar lavage (BAL) cells were identified as typical dendritic cells (DC), having an irregular outline, lobulated nucleus, and clear distinguishable acid phosphatase activity or EBM11 (anti-CD68) reactivity in a spot near the nucleus. After DC enrichment, using transient adherence to plastic, FcR-panning, and a density metrizamide gradient, a population containing 7-8% typical DC was obtained. This DC-enriched low density fraction, containing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…DCs purified from normal BAL induce 5 to 10 times more T cell proliferation than alveolar macrophages. This result has been replicated using multiple DC purification techniques including ''high-tech'' bead selection and cell sorting (63), and ''low-tech'' density gradient fractionation (43,64,65). While DCs have not yet been isolated from sarcoidosis BAL fluid for functional studies, it is likely that they are more immunostimulatory than sarcoidosis alveolar macrophages.…”
Section: Dcs Are More Immunostimulatory Than Macrophagesmentioning
confidence: 87%
See 1 more Smart Citation
“…DCs purified from normal BAL induce 5 to 10 times more T cell proliferation than alveolar macrophages. This result has been replicated using multiple DC purification techniques including ''high-tech'' bead selection and cell sorting (63), and ''low-tech'' density gradient fractionation (43,64,65). While DCs have not yet been isolated from sarcoidosis BAL fluid for functional studies, it is likely that they are more immunostimulatory than sarcoidosis alveolar macrophages.…”
Section: Dcs Are More Immunostimulatory Than Macrophagesmentioning
confidence: 87%
“…DCs only constitute approximately 1% of BAL fluid, as defined by lower FSC and SSC, and high expression of both MHC class II receptor HLA-DR and myeloid lineage integrin CD11c (34,43). This relative paucity of DCs in the BAL does not, however, reflect a lack of DCs in the airway.…”
Section: Myeloid Dendritic Cells In Sarcoidosis Dcs In Bal Fluid Are mentioning
confidence: 98%
“…In an early report involving anergic sarcoidosis patients, reduced numbers of epidermal Langerhans cells were found in both lesional and non-involved skin, with the most marked reductions seen in patients with multi-systemic disease (28). Later investigators have detected DCs in bronchoalveolar washings from sarcoidosis patients (29). More recently, it was shown that airway mDCs from sarcoidosis patients had increased expression of CD80 and decreased expression of CD86 compared to normal healthy volunteers, although overall DC numbers were comparable between the two groups (30).…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary DCs (18), which modulate the asthmatic inflammation (17), were recently characterized in the human lung (18)(19)(20)(21)(22). The functional subset of myeloid DCs (mDCs) plays a key role in inducing and maintaining an adaptive immune response to allergens in the lung (23).…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%